AN INQUIRY INTO GOVERNANCE AND ECONOMIC HARDSHIP IN NIGERIA: IMPLICATIONS FOR MIGRATION - Ikonne, Ogadinma (African Journal of Social and Behavioural Sciences, 2024)
This study was opinion paper focusing on an inquiry into governance and economic hardship in Nigeria with regards to how it affected migration. The study was aimed at exposing how governance was a major factor in the economic hardship in Nigeria and the extent to which this has resulted in migration of Nigeria’s productive citizens into other countries. The study was explained using a combination of the Institutional Theory by Douglass North (1990); the New Economics of Migration Theory by Michael Piore (1970) and the Malthusian Theory. The materials for this study were generated through secondary sources such as journals, books, book chapters, newspapers and internet sources while the content analysis and interrogation of the data was purely a critical one. The outcome of the interrogation showed that a lot of both skilled and unskilled Nigerians (but largely the skilled and educated ones), who are mainly young adults, have left the country, with a great number still making efforts to leave because of hardship orchestrated by poor governance and endemic corruption in government. Again, poor governance has negatively affected the welfare of the citizens with the multiplier effects of hunger, unemployment, poor educational system, insecurity, riots, increase in the prices of goods and services, loss of value to the nation’s currency and emigration of citizens in search of greener pastures, and the worst of it all was brain drain. It was also found that the emigrations of skilled and educated citizens have grave consequences for the country’s socioeconomic development. It was therefore recommended that Economic and Financial Crime Commission (EFCC) should be further quipped with honest personnel and model gadgets to be able to track, arrest and retrieve the stolen Nigeria’s money. This will go a long way to preserve a lot of money and resources that will be used for the benefit of the citizens.